(3cJGH QhVI GdYWQs - (3eMeO Hf eMehO Hf MGLj GdTQhGfj (B( (3GdTjQhGfj (B)s
(3ChdgG (B:s
(3GdaUd GdYGTQ ai eYQaI GdChRGf hGdcGjd ef cJGH QhVI GdYWQ ddTjN GdTQhGfi hgh eQJH Ydi MQha GdgLGA s
(3BNQgG (B:s
(3MQa GdgGA gGejf NeSI CSJGQ hGQHYI hYTQhf gh NeS SJI CbSGW QhejI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3gPg GdfSNI gi GdaUd GdYGTQ ef GdeNWhWIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B928s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs